ضوابط الأداء السيشي لذى صحفيي الإذاعات المرئية - جبالى,ندى; بريم,كريمة; باحمي,فاطمة الزهرة (University of Eloued جامعة الوادي, 2024)
هدفت هذهالدراسةالى معرفةضوابط الأداءالمهني لدى صحفي الإذاعات المرئية وذلك بدراسةميدانيةعلى صحفي إذاعةالتحريروإذاعةالجديدبولاية -الوادي- وقد شملت 40 صحفيإذاعةالتحريروإذاعةالجديدبولايةالواديلإجراءالدراسةحولهما،كذلك تم تحديد ا دوات جمع البيانات،وتم الاعتماد على المنهج المسحي وأداةالاستبيان والملاحظة بغيت الوصول الى الأهداف التالية: - التعرف على اهم الضوابط التي تحكم الأداء المهني لدى صحفي الإذاعات المرئية (الالكترونية) - التعرف على مدى دراية الصحفيين بالضوابط المهنية. - التعرف على اهم مؤشرات الأداء المهني في الإذاعات المرئية (الالكترونية). - التعرف على مدى التزام صحفيو الإذاعات الالكترونية بالضوابط الإعلامية. ولقد وصلنا من خلال الدراسة الميدانية الى النتائج التالية أهمها: - صحفي الإذاعات المرئية الالكترونية يلتزمون بالضوابط المهنية و الأخلاقية و القانونية . - صحفي الإذاعات المرئية الالكترونية لديهم معرفة بالضوابط الأخلاقية و القانونية . This study aimed to find out the controls of professional performance of video broadcast journalists through a field study on the journalists of radio Tahrir and new radio in the state of –EL-OUED. It included 40 journalists of radio Tahrir and new radio in the state of EL-OUED to conduct the study about them. The data collection tools were also identified, and reliance was placed on. The survey method, questionnaire and observation tool aimed to achieve the following objectives: - Identifying the most important controls that govern the professional performance of a video (electronic) radio journalist. -Identifying the extent of journalists’ knowledge of professional controls. - Identify the most important indicators of professional performance in visual (electronic) radio. - Identify the extent to which electronic radio journalists adhere to media controls. Through the field study, we reached the following results, the most important of which are: -Electronic visual broadcasting journalists adhere to professional, ethical and legal regulations. -Electronic visual radio journalists have knowledge of ethical and legal controls. -Electronic video broadcasting journalists have knowledge of professional regulations
الالكترونية
Keywords: - صحفي الإذاعات المرئية الالكترونية لديهم معرفة بالضوابط المهنية